STRATEGI PENGEMBANGAN TANAMAN NANAS (Ananas comosus) DI KELURAHAN BUKIT MERDEKA KECAMATAN SAMBOJA KABUPATEN KUTAI KARTANEGARA - Rita Mariati; Eko Harri Yulianto; Rujiah Andraini (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
Pineapple is a horticultural crop that has bright potential and prospects and is an activity to improve the agricultural sub-sector in Indonesia. Bukit Merdeka Village is one of the pineapple-producing areas in East Kalimantan. However, the development of pineapple in Bukit Merdeka Village was slightly disturbed by the development of government infrastructure. This research was conducted to determine the factors that influence the development and strategy of pineapple plant development in Bukit Merdeka Village. The research was carried out from April 2022 to July 2022 in Bukit Merdeka Village, Samboja District, Kutai Kartanegara Regency. The data used in this study are primary data and secondary data. The sampling method was carried out by simple random sampling with 36 respondents from a total farmer population of 250 pineapple farmers. The data of this study were analyzed using SWOT. Based on the SWOT analysis shows the results of the matrix calculation, the IFAS score is 1.58 and the EFAS score is -0.86, which means that the development strategy is in quadrant II, namely the ST strategy or supports the diversification strategy of a business that diversifies the types of businesses, which can be done to increase Production and profit for farmers is to maintain product quality and expand information to enter selective markets so that they can compete with other pineapple producers. The results showed that the internal factors in pineapple farming in Bukit Merdeka Village were land availability, product quality and availability, farming experience, capital, lack of technology, non-uniform production results, poor planning, and financial records, while external factors were product demand, easy to obtain seeds, pineapple producing centers, IKN buffer areas, pest and disease attacks, unpredictable weather, rising costs of pesticide fertilizers, inadequate road infrastructure, and fluctuating prices.